RURAL ONE-PERSON HOUSEHOLDS – CHARACTERISTICS, INCOME AND CONSUMPTION - Marlena Piekut (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The aim of the study was to identify the structure of rural one-person households due to sociodemographiccharacteristics and living conditions in these households. The subject of the research isincome and expenditure on consumer goods and services. Living conditions in one-person households inrural areas are worse than in the city.